Social capital and the transition to democracy - Bădescu, Gabriel, 1969-; Uslaner, Eric M. (London ; New York : Routledge, 2003)
This edited collection presents the latest quantitative research on how post-communist countries are adapting to Western models of society.
Introduction / Gabriel Badescu and Eric M. Uslaner -- Trust networks and democratic transition : Yugoslavia in the mid-1980s / Hajdeja Iglic -- Communist societies, the velvet revolution, and weak ties : the case of East Germany / Henk Flap and Beate V"olker -- Social networks in Russian politics / Nicolas Hayoz and Victor Sergeyev -- Social networks, civil society, and the prospects for consolidating Russia's democratic transition / James L. Gibson -- Trust and civic engagement in East and West / Eric M. Uslaner -- Social capital and support for democracy in the post-communist states / Kathleen M. Dowley and Brian D. Silver -- Social trust and democratization in the post-communist societies / Gabriel Badescu -- Civic engagement in a post-communist state / Jeffery J. Mondak and Adam F. Gearing -- Why post-communist citizens do not join voluntary organizations? / Marc Morj Howard -- Social capital in Poland / Jerzy Bartkowski -- What does social capital add to democratic values? / Richard Rose and Craig Weller -- Legacies and conflicts : the challenges to social capital in the democratic transition / Eric M. Uslaner and Gabriel Badescu.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Democratization -- Europe, Eastern; Democratization -- Europe, Central; Democratization -- Former Soviet republics; Social capital (Sociology) -- Europe, Eastern; Social capital (Sociology) -- Europe, Central; Social capital (Sociology) -- Former Soviet republics; Démocratisation -- Europe de l'Est.; Démocratisation -- Europe centrale; Démocratisation -- Ex-URSS.; Capital social (Sociologie) -- Europe de l'Est.; Capital social (Sociologie) -- Europe centrale; Capital social (Sociologie) -- Ex-URSS.; POLITICAL SCIENCE -- Political Process -- General; Democratization; Social capital (Sociology); Central Europe; Eastern Europe; Soviet Union -- Former Soviet republics